Lifestyle and health conditions of adults with spinal cord injury - Sátiro Xavier de França, Inacia; Cruz Enders, Bertha; Silva Coura, Alexsandro; Pereira Cruz, Giovanna Karinny; da Silva Aragão, Jamilly; Carvalho de Oliveira, Déborah Raquel (Investigación y Educación en Enfermería, 2014)
Objective. To describe the lifestyle of adults with spinal cord injury and explore its relation with some health conditions. Methodology. Cross sectional study, in which a questionnaire containing sociodemographic, habits and health conditions variables was used. Forty-seven people with spinal cord injury participated and answered the self-report questionnaire. Results. The group under study was predominantly male (92%), under 40 years of age (47%), and had low educational level (76%). The most frequent risk factors related to the lifestyle were: smoking (28%), alcohol consumption (36%), coffee consumption (92%) and being physically inactive (64%). Association was found between having four or more risk factors related to lifestyle and the loss of appetite, as well as constipation. Conclusion. The actual inadequate lifestyle is associated with the health conditions of patients, and the nursing team should pay special attention to the education and promotion of health related to people with spinal cord injury.